Ella Fitzgerald : an annotated discography : including a complete discography of Chick Webb - Johnson, J. Wilfred, 1920- (McFarland & Co., 2010)
Ella Fitzgerald was one of America's greatest jazz singers. This volume is as complete a discography of her recorded songs as currently seems possible to compile. This volume also contains a complete discography (1927-1939) for drummer and bandleader Chick Webb, with whom Ella began her recording career in 1935. Part One includes a chronological listing of all known recorded performances of both Chick Webb and Ella. Part Two gives the complete contents of Ella's LPs and CDs, including track listings, titles (with lyricists and composers) and timings. Part Three is an annotated alphabetical listing of all songs contained on all of Fitzgerald's records, with detailed information on each song's composer, lyricist, and history. Reviews of the movies in which Ella appeared and surveys of her career with the Decca, Verve and Pablo music companies are included. The book also has an index of album and CD recordings, and composers, lyricists and musicians.